Film festivals in Africa: a study in sustainability - Utian-Preston, Lara (Centre for Film and Media Studies, 2023)
The sustainable future of film festivals in Africa is a vital issue based on the critical role that film festivals play in African filmmaking, and yet has not been widely investigated. This thesis identifies four key factors that I argue are essential to this sustainable future. These factors are: community and identity, the various mechanisms by which a festival's selfdefined identity or brand is developed and expressed; physicality and place, the concept of the lived and physical spatial nature of film festivals; technology, how innovations in technology are having an impact on film festivals; and financing and funding, the ability of film festivals to attract funding and finance. Each of these factors is discussed from both a theoretical perspective that draws on the history of film festivals as well as relevant areas of scholarship. Additionally, this thesis draws upon my years of professional experience working with film festivals in Africa. Through this auto-ethnographic approach I am able to complement the theoretical analysis of each of these factors with real-world examples and applications. This investigation makes it clear that the trajectory of African film festivals is distinctly different to those in the West, mainly due to localised factors such as the lack of cinema infrastructure and accessible internet connectivity, but also due to the existence of a global film festival hierarchical network, within which film festivals in Africa sit near the bottom. It is also apparent from this analysis that to become sustainable film festivals in Africa must effectively leverage these four factors through authentic claims to community and identity, accessible physical spaces, adaptation and inclusion of technology and disruption, and a diversity of funding models.